Analysis of Bilingual Learning Theories and References (Methods, Techniques, Strategies, Evaluation) - Apriliana, Zahra; Kamilah, Ashha Fithriya; Sugihwarni, Popy; Sari, Choirul Novita; Sakdiyah, Labiibah Lathifatus; Zaharani, Nur Erissya; Widagdo, Arif (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The use of two languages of instruction in bilingual classes, English and Indonesian, in the process of teaching and learning activities is certainly not an easy thing. Teachers must be able to choose the right learning theory and the right and clear learning references, so that the bilingual learning that will be implemented can run well. can run well. In the implementation of bilingual learning, there are special designs, plans, or stages that are mature so that the learning process can take place optimally. The design of bilingual learning can be interpreted from various perspectives, such as discussing various studies and theories regarding the strategy and process of learning development and implementation. The result of this study shown that Bilingual learning involves the use of two languages, usually the mother tongue and English, to enhance cognitive abilities, creativity, problem solving and socio-cultural understanding. Bilingual education requires careful planning, with teachers who are proficient in both languages and schools that provide the necessary resources such as teaching materials and infrastructure. Bilingual learning starts with basic vocabulary and simple conversation. The curriculum focuses on real-world words and phrases, which gradually helps students become fluent in both languages, so they can switch from one to the other with ease. Theoretical frameworks, such as the Global English Club approach, support bilingual education through methods such as group discussions and real-world learning experiences. Bilingual learning methods, including the Transition, Maintenance, Enrichment and Legacy approaches, aim to meet students' needs and curriculum objectives. Activities such as role-playing and group discussions further reinforce language retention and active learning in both academic and real-life contexts. Regular evaluation of student progress is necessary for continuous improvement in teaching and learning outcomes.